THE INFLUENCE OF CUSTOMERS PERSPECTIVES AND PREFERENCES ON THE CUSTOMER-ORIENTED BANK MARKETING MIX STRATEGIES - Anak Agung Putu Agung (Journal of Economics, Business, and Accountancy Ventura, 2013)
This study examines the influences of the customers’ perspectives and preferences on the customerorientedmarketing mix strategies implemented by the PT Bank Pembangunan Daerah Bali. Theresult showed that the customers’ perspective exerts a significant influence on the design of themarketing strategy, the customers’ preferences have a significant influence on the design of themarketing strategy, and the design of the marketing strategy has a beneficial influence upon themarketing mix strategy. The results of the test supported the theory on the marketing strategy process.The theory espoused that the activities to adopt the customers’ perspectives and preferences, inorder to find out about their wants and needs, and the activities to devise a marketing strategy design,and the activities to implement the marketing mix strategy, should be treated as integratedactivities because the three of them were one unified and comprehensive marketing strategy. Thestudy provides the management of this Bank with a source of inspiration to be more pro-active inmanaging customer-oriented marketing strategies. It can be achieved by conducting a more integratedmarketing activities based on a marketing strategy process. This marketing strategy shouldalso be developed in BPD all across Indonesia as a strategic response to create a sustainable competitiveedge in the increasingly competitive world of today’s banking sector.